Neutrophilic granulocytes – promiscuous accelerators of atherosclerosis - Drechsler, Maik; Döring, Yvonne; Megens, Remco T. A.; Soehnlein, Oliver (Thrombosis and Haemostasis, 2011)
Neutrophils, as part of the innate immune system, are classically described to be main actors during the onset of inflammation enforcing rapid neutralisation and clearance of pathogens. Besides their wellstudied role in acute inflammatory processes, recent advances strongly indicate a so far underappreciated importance of neutrophils in initiation and development of atherosclerosis. This review focuses on current findings on the role of neutrophils in atherosclerosis. As pro-inflammatory mechanisms of neutrophils have primarily been studied in the microvascular environment; we here aim at translating these into the context of macrovascular inflammation in atherosclerosis. Since much of the pro-inflammatory activities of neutrophils stem from instructing neighbouring cell types, we highlight the promiscuous interplay between neutrophils and platelets, monocytes, T lymphocytes, and dendritic cells and its possible relevance to atherosclerosis.
Keywords: Atherosclerosis; neutrophil; inflammation; recruitment